Ultra Deep Catalogue of Galaxy Structures in the Cosmic Evolution Survey field - Söchting, Ilona K. (2012)
This paper presents a large sample of intermediate- to high-redshift galaxy groups and clusters detected using a fully automated search in the Cosmic Evolution Survey field. The detection algorithm is based on density peak extraction from a density distribution sampled using Voronoi tessellation within overlapping slices in the photometric redshift space. The cluster catalogue contains 1780 structures covering the redshift range 0.2 < z < 3.0, spanning three orders of magnitude in luminosity (10 8 < L 4 < 5 × 10 11L ⊙) and richness from eight to hundreds of galaxies. All clusters at z > 0.4 and many even below this threshold show very prominent substructure indicating that z~ 0.4 marks the slow emergence of virialized clusters in this field in agreement with published findings for other regions of the sky. The redshift distribution of detected structures shows strong variations with prominent peaks suggesting the presence of large-scale structures across the whole range covered by this catalogue. Supercluster candidates have been identified at redshifts z= 0.35, 0.72, 0.94, 1.12, 1.27, 1.45, 2.0 and 2.52. At z= 2.9 we identified a compact agglomeration of galaxy groups and clusters suggesting the presence of another supercluster-like structure which has been the highest redshift candidate so far. Out of the nine supercluster candidates found in this study, six are new detections.